Adverse fetal outcome in road accidents: Injury mechanism study and injury criteria development in a pregnant woman finite element model. (December 2016) - Auriault, F.; Thollon, L.; Pérès, J.; Behr, M.
Highlights: A total of 8 different accident scenari were simulated with a finite element pregnant woman model. Several possible injury predictors were compared to real car accident cases reported in literature. Intra uterine pressure in the neighbourings of placenta was found as highly correlated to the fetal outcome. Abstract: This study documents the development of adverse fetal outcome predictors dedicated to the analysis of road accidents involving pregnant women. To do so, a pre-existing whole body finite element model representative of a 50th percentile 26 weeks pregnant woman was used. A total of 8 accident scenarios were simulated with the model positioned on a sled. Each of these scenarios was associated to a risk of adverse fetal outcome based on results from real car crash investigations involving pregnant women from the literature. The use of airbags and accidents involving unbelted occupants were not considered in this study. Several adverse fetal outcome potential predictors were then evaluated with regard to their correlation to this risk of fetal injuries. Three predictors appeared strongly correlated to the risk of adverse fetal outcome: (1) the intra uterine pressure at the placenta fetal side area (r = 0.92), (2) the fetal head acceleration (HIC) (r = 0.99) and (3) area of utero-placental interface over a strain threshold (r = 0.90). Finally, sensitivity analysis against slight variations of the simulation parameters was performed and assess robustness of these criteria.